- 267

- 3

This is what I'm given:

(9x[tex]^{2}[/tex]+y-1)

*dx*- (4y-x)

*dy*=0 y(1) =3

Solve the initial value problem and determine at least where the solution is valid.

I did solve the problem, but I end up with this:

A.) 3x[tex]^{3}[/tex]+xy-x-2y[tex]^{2}[/tex]=2

When my calculator solves for Y, I get the same answer as the book does. However, I'm rather stumped at

*how*the book gets this answer:

B.) y = [x - (24x^3+x^2-8x-16)[tex]^{1/2}[/tex]] / 4.

Can anyone help me to get from point A to point B? Thanks.